Diversity of Mycosphaerella spp. and Teratosphaeria spp. in Eucalyptus globulus plantations in Brazil - Passador, Martha Maria [UNESP]; de Lima, Patrícia Rodrigues; de Pieri, Cristiane [UNESP]; Sierra-Hayer, Juan Fernan [UNESP]; Harakava, Ricardo; Furtado, Edson Luiz [UNESP] (Springer Nature, 2013)
Among the most important diseases affecting Eucalyptus is Mycosphaerella Leaf Disease (MLD) caused by Mycosphaerella spp. and Teratosphaeria spp. MLD has led to significant losses in eucalypt plantations in the South and Southeast Region of Brazil, as well as in several countries such as Portugal, Spain, South Africa and Australia. Symptoms of MLD include localized necrotic spots, early defoliation in juvenile plants, stem cankers, early death of branches, and in some cases, atrophy and death. In the present study, single spore isolations from leaves of E. globulus from five locations in Brazil allowed the differentiation of species of Mycosphaerella and Teratosphaeria based on ascospore germination and growth in culture. These isolates were also subjected to sequence analysis of the ribosomal RNA internal transcribed spacer regions, which allowed their identification to species level. The results of this study showed that six species of Mycosphaerella and four species of Teratosphaeria were associated with leaves showing symptoms of MLD in E. globulus plantations in various locations of Brazil. © 2013 KNPV.
Keywords: Ascospores and germination; ITS region; Single spore isolation; Symptoms; defoliation; disease; fungus; germination; isolation effect; juvenile; leaf morphology; plantation; RNA; species diversity; spore; tree; Australia; Brazil; Croatia; Portugal; South Africa; Spacva; Spain; Bacteria (microorganisms); Eucalyptus; Eucalyptus globulus; Mycosphaerella; Teratosphaeria